Surface electromyography of the vastus lateralis and gluteus medius muscles in post-operative T3–L3 hemilaminectomy dogs: a prospective controlled observational study - Schwartz, John A.; Carrera-Justiz, Sheila; Repac, Jennifer A. (Frontiers in Veterinary Science, 2024)
The objective of this study was to determine if surface electromyography (sEMG) demonstrates differences in muscle activation between normal and dogs recovering from spinal cord injury due to intervertebral disc extrusion. Animals: Two groups of client-owned small-breed chondrodysplastic-type dogs were tested. Group 1 consisted of seven ambulatory paraparetic dogs that had undergone a hemilaminectomy procedure in the T3-L3 region for intervertebral disc extrusion one month prior. Group 2 was made up of seven normal dogs that had no history of intervertebral disc disease or spinal surgery. Procedures: Each subject walked 10 feet on a nonslip surface for at least 5 gait cycles for the sEMG to capture muscle activation of the vastus lateralis and gluteus medius, bilaterally. Muscle activation was quantified as the total myoelectric output area under the curve, averaged across all gait cycles. Results: Muscle activation was significantly greater in the post-operative hemilaminectomy group (P = 0.012). There was a significant difference in muscle activation between each hindlimb in the postoperative hemilaminectomy group, but not in the normal group. The muscle activation was significantly lower on the side that underwent surgery compared to the opposite limb (P = 0.0034).Post-operative hemilaminectomy dogs have greater hindlimb muscle activation compared to normal dogs, which likely represents a lack of descending inhibition secondary to upper motor neuron syndrome. The side of surgery is correlated with decreased muscle activation. Surface EMG can be used to evaluate muscle activity in dogs recovering from spinal decompression surgery.